2018
DOI: 10.1002/advs.201800420
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination‐Enhanced Ambient Stability and Electronic Tolerance of Black Phosphorus Quantum Dots

Abstract: The environmental instability and uneliminable electronic trap states in black phosphorus quantum dots (BPQDs) limit the optoelectronics and related applications of BPQDs. Here, fluorinated BPQDs (F‐BPQDs) are successfully synthesized by using a facile electrochemical exfoliation and synchronous fluorination method. The F‐BPQDs exhibit robust ambient stability and limited fluorination capability, showing a nonstoichiometric fluorination degree (D F) maximum of ≈0.68. Density functional theory calculations conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 74 publications
0
56
0
Order By: Relevance
“…Due to its unique electronic and optical properties, 2D BP has been widely studied in many research fields [114,120,[122][123][124][167][168][169][170][171][172][173][174]. Furthermore, it has been reported that it exhibits an ultrahigh Seebeck coefficient in the order of 10 mV K −1 , which makes it a promising thermoelectric materials.…”
Section: Thin-film Thermoelectric Materialsmentioning
confidence: 99%
“…Due to its unique electronic and optical properties, 2D BP has been widely studied in many research fields [114,120,[122][123][124][167][168][169][170][171][172][173][174]. Furthermore, it has been reported that it exhibits an ultrahigh Seebeck coefficient in the order of 10 mV K −1 , which makes it a promising thermoelectric materials.…”
Section: Thin-film Thermoelectric Materialsmentioning
confidence: 99%
“…The surface functionalization by P−F bonds led to the improvement of BP stability in the air as well as high potential in photothermal applications where are combined excellent absorption properties, low toxicity, and improved stability towards oxidation. The stabilization effect was observed for electrochemically exfoliated and fluorinated black phosphorus quantum dots . For the other pnictogens was the possible functionalization with halogen and hydrogen discussed only theoretically using DFT calculations .…”
Section: Modificationsmentioning
confidence: 99%
“…Thes tabilization effect was observed for electrochemically exfoliated and fluorinated black phosphorus quantum dots. [24] Fort he other pnictogens was the possible functionalization with halogen and hydrogen discussed only theoretically using DFT calculations. [25] Thea rsenene-based system was studied in detail with one-site halogenation and one-site hydrogenation.…”
Section: Covalent Modificationsmentioning
confidence: 99%
“…The efficient photothermal conversion makes them advantageous for photothermal evaporation, but their photo‐degradability should be considered for practical applications. There have been a vast number of strategies working on enhancing the stability of phosphorene, including covalent bonding via aryl diazonium, surface coordination of titanium sulfonate ligand, fluorination, alkali metal‐intercalation, metal‐ion passivation, and package by graphene shell, hexagonal BN, organic monolayers, graphene oxide (GO), AlO x , etc. Searching for other phosphorene‐analogue alternatives provide another avenue for photothermal evaporation .…”
Section: Photothermal Evaporationmentioning
confidence: 99%